Steering Assist Control for Bicycles with Variable Trail Effect - Takaatsu Kihara; Yuzuki Sugasawa; Keigo Kuriyama; Masami Iwase (Applied Sciences)
The purpose of this study is to realize a power steering control that restores the maneuverability of the bicycle by assisting in handlebar operation during loading according to the analysis of the effect of loading children and luggage in the front basket on maneuverability. Placing baggage and child in the front basket of a bicycle causes an increase in the moment of inertia around the handlebar axis and a change in the position of the center of gravity, and leads to a decrease in the maneuverability of the bicycle. To solve the issue, previous studies have contributed to improve the maneuverability by applying the assist torque proportional to the user’s steering one by a power steering mechanism. However, in general, bicycle steering is affected not only by handlebar operation but also by the roll angle of the bicycle body through the trail effect. Therefore, in this study, we propose to design a control system to realize the variable trail effect, which is related to the roll angle of the bicycle body, and use it as the steering assist. To verify the effectiveness of the proposed method, we developed a bicycle equipped with the power steering mechanism and implemented the proposed control algorithm. The behavior of the experimental bicycle during straight-line and slalom biking has been analyzed, and it has been shown that the control system with the variable trail effect can recover maneuverability when a weight is placed in the front basket.